Teacher Perceptions In Implementing The Curriculum Merdeka - Desna Yarlina Telaumbanua (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This research describes how teachers perceive the implementation of the independent curriculum in School. This research is qualitative research. Qualitative research is research that explore and understand the meaning a number of individuals or groups of people derive from social problems. Researchers construct reality and understand its meaning, so this research pays great attention process, event, and authenticity. Respondents are teachers at school. Data collection in this research was through interviews. The main instrument of this research is the researcher supported by field notes. All data is collected and studied descriptively to obtain reliable and reliable findings. Research result shows that: (1) teachers' perceptions are positive and appreciative of the implementation of the Merdeka Curriculum in schools, (2) teachers have an important role in the process of curriculum development and implementation in schools and success in implementing the curriculum really depends on how intense the teacher is in implementing the curriculum in the classroom; (3) teachers have the ability to develop and implement curriculum and class design, in order to improve the quality of teaching and learning processes; (4) There has not been optimal socialization and specific training regarding the formation of student profiles Pancasila; and other.